Investigation of Snow Deposition on the Railway Cuttings During the Snowdrift - Ma, Wenyong; Li, Sai; Sun, Yuanchun; Li, Jianglong; Li, Feiqiang (Frontiers in Earth Science, 2022)
This study confirmed a mixture multiphase model based on the Euler–Euler method to predict snow deposition in road cuttings. A scaled model experiment was conducted in the Mayitas region of Xinjiang to verify the numerical simulation accuracy, which revealed a good agreement. Regarding the formation mechanism of drifting snow disasters in road cuttings, the wind speed in the simulation results was analyzed in detail. The results indicated that the low-wind speed area is positively correlated with the vortex size and that snow deposition occurs between the vortex separation point and vortex reattachment point. The appearance and disappearance of the secondary vortex can divide the snow cover process into three stages, and the second phase after secondary vortex emergence represents the period of a rapid increase in the snow thickness. Snow cornices are the leading emergence cause of secondary vortex. The related critical snow storage capacity should also be considered to measure the snow storage capacity of road cutting types.